Exaggerated postnatal surge of orexin neurons and the effects of elimination of excess orexin on blood pressure and exaggerated chemoreflex in spontaneously hypertensive rats - Lusk, Savannah; Moushey, Alexander M.; Iwakoshi, Nicholas; Wilson, Christopher G.; Li, Aihua; Ray, Russell (Frontiers in Physiology, 2024)
An overactive orexin (OX) system is associated with neurogenic hypertension and an exaggerated chemoreflex in spontaneously hypertensive rats (SHRs). However, the chronology and mechanism of this association is unclear. We hypothesized that increased postnatal neurogenesis of OX neurons in SHRs precedes and contributes to the aberrant increase in mean arterial blood pressure (MAP) and the exaggerated response to hypercapnia during postnatal development. We found that both SHRs and Wistar-Kyoto (WKY) rats experienced postnatal increases in the number of OX neurons. However, SHRs experienced a greater increase than WKY rats before P15, which led to significantly more OX neurons in SHRs than age-matched WKY controls by P15-16 (3,720  780 vs 2,406  363, p=0.005). We used bromodeoxyuridine (BrdU) to determine if the postnatal increase was from increased neurogenesis or maturation of existing neurons. We found that neurogenesis, as evidenced by strong BrdU staining in OX-positive neurons, was the primary contributor to the excess of OX neurons in SHRs during early postnatal development. While SHRs develop more OX neurons by P15-16, SHRs and normotensive WKY control rats have similar MAP during postnatal development until a significantly higher MAP emerges at P25 in wakefulness (81.6 ± 6.6 vs 67.5 ± 6.8 mmHg, p=0.006) and sleep (79.3  6.1 vs 66.6  6.5, p=0.009), about 10 days after the surge of OX neurons. To determine the contribution of excess OX neurons in SHRs to the rise in MAP, we used OX neuron-targeted saporin toxin to eliminate OX neurons between P30 and P40 in the hypothalamus of SHRs. By selectively eliminating excess ( 30%) OX neurons in SHRs, we saw a significantly lowered MAP and hypercapnic ventilatory chemoreflex compared to non-lesioned SHRs at P40. We suggest that the postnatal increase of OX neurons, primarily attributed to exaggerated postnatal OX neurogenesis, may be necessary for the development of higher MAP and exaggerated chemoreflex in SHRs, and modulation of the overactive OX system may have a potential therapeutic effect during the pre-hypertensive period.